Tlingit painted grave box, Sitka area, Alaska, in engraving made 1837 - University of Washington Libraries
Photograph of engraving of painted grave box Caption on image: Tomb Image from Edward Belcher's Narrative of a voyage round the world, 1843, v.1, p. 104